Chitosan-coated MIL-100(Fe) nanoparticles for enhanced piperine release in breast cancer treatment - Quijia, Christian Rafael [UNESP] (2024)
Breast cancer is one of the leading causes of death among women with cancer worldwide. Piperine (PIP) is a promising compound with potential chemotherapeutic activity for the treatment of breast cancer due to its antitumor activity, but its toxicity has limited its introduction in preclinical studies. An attractive platform for the treatment of breast cancer is represented by PIP@MIL-100(Fe), a metal-organic framework (MOF) network encapsulated with PIP and used as a release system. An engineering strategy in nanotechnology is the surface modification of nanosystems, such as chitosan (CHI), which is used to increase resistance to degradation and enable controlled drug release. Based on these scientific and technological advances, the aim of this study is to evaluate the therapeutic potential of PIP encapsulated in metal-organic frameworks coated with CHI in the treatment of breast cancer. The CHI@PIP@MIL-100(Fe) was successfully synthesized, which consists of MIL-100(Fe) containing PIP and coated with CHI, using the impregnation method. The infrared spectroscopy analysis showed major absorption bands such as the saccharide structure (1042, 1092, and 1164cm−1), confirming the presence of CHI in the MOFs. The cytotoxicity tests conducted on breast cancer cells, including SKBR3, MCF-7, MDA-MB-231, and BT549, using CHI@PIP@MIL-100(Fe), exhibited lower cytotoxicity indices in comparison to free PIP, which showed an index that was three to four times higher. Therefore, these nanostructures show potential as PIP-based therapies for breast cancer.